Studi fenomenologi: Makna dari kesejahteraan bagi lanjut usia - Lilyana, Maria Theresia Arie; Cempaka, Anindya Arum (Poltekkes Kemenkes Kupang, 2023)
Introduction: Elderly is the final period of human growth and development, changes occur in terms of physical, psycho, social and spiritual will become more mature. These changes require the ability of the elderly to adapt to the changes experience, so that they are satisfied undergoing their life, and ultimately have an impact on well-being. Objective: Determine the meaning of well-being for the elderly. Method: Qualitative research with 12 participant who met the inclusion criteria until saturated data. Data collection was carried out by in-depth interviews using a voice recorder and guided question. The results of the interviews were followed by verbatim transcripts and data analysis using Colaizzi’s to produce research themes that would be described as research results. Result: The theme in this study is the meaning of well-being for the elderly, factors supporting feelings of well-being and activities that support feelings of well-being.